Ensino primário tipicamente rural no Estado de São Paulo: um estudo sobre as Granjas Escolares, os Grupos Escolares Rurais e as Escolas Típicas Rurais (1933-1968) - Moraes, Agnes Iara Domingos [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
In this work it is presented the research results of master's degree in education, with the overall objective of restoring aspects of the history of rural elementary school in the State of São Paulo, focusing the Granjas Escolares, Grupos Escolares Rurais and Escolas Típicas Rurais, implemented over the period from 1933 to 1968. Through historical approach, focused on bibliographic and documentary research, using as documentary corpus two educational journals – Journal of Education from 1933 to 1961 and the journal of Professor from 1934 to 1965; the annuaries of teaching in the State of São Paulo from 1935 to 1936 and from 1936 to 1937; the annual reports of the Regional Departments of education from 1933 to 1945; the messages of the Governors of the State of São Paulo; Federal legislation over 1933 and 1967; State legislation that regulated the rural education over 1933 and 1968 and theme-related books produced and in circulation in the period defined for the research. The results indicate that the studied schools were projected to meet the pressing demands on the historical moment of its implementation. These demands were related to the formation of a national identity, attachment of the man in the field, the sanitation diffusion, training for work, among others. The three types of schools studied represented a very restricted number of rural elementary schools in the State of São Paulo in Brazil and they presented many points converged with ruralist conception of education.

Apresentam-se resultados de pesquisa de Mestrado em Educação, com o objetivo geral de reconstituir aspectos da história da escola primária rural no Estado de São Paulo, focalizandose as Granjas Escolares, os Grupos Escolares Rurais e as Escolas Típicas Rurais, implementadas no período de 1933 a 1968. Mediante abordagem histórica, centrada em pesquisa documental e bibliográfica, utilizam-se como corpus documental dois periódicos educacionais – a Revista de Educação de 1933 a 1961 e a Revista do Professor de 1934 a 1965; os Annuarios do Ensino do Estado de São Paulo de 1935-1936 e 1936-1937; os Relatórios anuais das Delegacias Regionais de Ensino de 1933 a 1945; as Mensagens dos Governadores do Estado de São Paulo; a Legislação Federal entre 1933 e 1967; a Legislação estadual que normatizava a educação rural entre 1933 e 1968 e livros relacionados à temática produzidos e em circulação no período delimitado para a pesquisa. Os resultados apontam que as escolas estudadas foram concebidas visando o atendimento de demandas prementes no momento histórico de sua implementação. Essas demandas estavam relacionadas à formação de uma identidade nacional, fixação do homem no campo, difusão do sanitarismo, formação para o trabalho, entre outras. As três modalidades de escolas estudadas representaram um número bastante restrito no conjunto das escolas primárias rurais do Estado de São Paulo e apresentaram muitos pontos convergentes com a concepção ruralista de educação.
Keywords: Escolas rurais - São Paulo (Estado) 1933-1968; Educação rural; Educação - Historia; Education, Rural